ANALISIS MANAJEMEN BISNIS SYARIAH PENGARUH POTONGAN HARGA, DISPLAY, KUALITAS PRODUK TERHADAP MINAT BELI DI ALFAMART RAYA CIBATOK, KECAMATAN CIBUNGBULANG, KABUPATEN BOGOR, JAWA BARAT - Lestari, Widi; Trihantana, Rully; Suryani, Ermi (Sahid Business Journal : Jurnal Penelitian Manajemen Bisnis Syariah: Program Studi Manajemen Bisnis Syariah, 2024)
The purpose of this research is to analyze and explain whether the independent variables (price discounts, product displays and product quality) have a positive and significant effect on the dependent variable (purchasing interest). The method used in this research is quantitative which is associative. The subjects of this research are customers who shop at Alfamart Raya Cibatok. The data analysis method used is multiple linear analysis. The results of this study show that (1) the significance value is 0.03 which is smaller (<) than 0.05. This means that there is a significant influence between price discounts and buying interest. (2) A significance value of 0.00 which is smaller (<) than 0.05. This means that there is a significant influence between product display and purchase intention. (3) A significance value of 0.00 which is smaller (<) than 0.05. This means that there is a significant influence between product quality and purchase intention. (4) Simultaneously FCount is 85.607 with a significance result of 0.000 and F table = F (k; n-k) ‎‎= F = (3;97) = 2.70 results show that FCount is 85.607 greater (>) than 2.70 and a sig value of 0.00 which is smaller (<) than 0.05. This means that price discounts, product displays, and product quality simultaneously have a significant influence on purchase intention. Furthermore, how much the independent variable explains the dependent variable is shown in the value of the coefficient of determination of 0.719 or 71.9%, buying interest can be influenced by price discounts, product displays and product quality and the remaining 28.1%, buying interest is influenced by variables other.‎